OPTIMALISASI PEMANFAATAN SMART CLASSROOM MELALUI MODEL SAMR UNTUK MENINGKATKAN LITERASI DIGITAL MAHASISWA CALON GURU SD - Muhamad Furqon Al Hadiq; Gilang Mas Ramadhan; Rian Syahvierul (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The growing demand for technology integration in education requires prospective elementary school teachers to possess strong digital literacy competencies. However, prior research shows that their ability to utilize technology for pedagogical purposes remains limited, potentially hindering the quality of teaching practices in the digital era. This study employed a quasi-experimental design using a Nonequivalent Control Group Design to examine the impact of implementing the SAMR (Substitution, Augmentation, Modification, Redefinition) model within a Smart Classroom environment. Two groups participated: an experimental group that received SAMR-based instruction and a control group that experienced conventional teaching. Digital literacy was measured using a validated and reliable questionnaire. The findings demonstrate that students in the experimental group achieved a higher improvement in digital literacy scores compared to those in the control group. The integration of SAMR stages enabled a gradual transformation of learning activities—from simple digital substitution to innovative, redefined practices—resulting in more meaningful technology use. These results confirm the effectiveness of the SAMR model as a framework for optimizing Smart Classroom facilities to systematically enhance digital literacy. The study highlights the importance of embedding structured technology-integration models in teacher education programs to prepare future educators for 21st-century learning environments.